2017
DOI: 10.4136/ambi-agua.1910
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização de parâmetros de qualidade da água na área portuária de Barcarena, PA, Brasil

Abstract: RESUMOEmpresas no pólo industrial do município de Barcarena-PA utilizam matérias primas, insumos e energia e geram resíduos sólidos, efluentes industriais e esgoto doméstico que são lançados em corpos receptores, alterando as suas características físicas, químicas e microbiológicas. Visando determinar a influência das empresas localizadas no pólo industrial de Barcarena, foi realizado um estudo em um trecho do Rio Pará que sofre influência do lançamento de efluentes industriais das empresas em operação. Para t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0
21

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 23 publications
(28 reference statements)
3
10
0
21
Order By: Relevance
“…The analyzed samples were above that established for natural waters (10 to 100 µS cm −1 ) according to the CONAMA legislation 357/05. An increase in electrical conductivity during the dry period was evident, which agreed with [28] who found that electrical conductivity decreased during the rainy season due to high ion-dilution.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The analyzed samples were above that established for natural waters (10 to 100 µS cm −1 ) according to the CONAMA legislation 357/05. An increase in electrical conductivity during the dry period was evident, which agreed with [28] who found that electrical conductivity decreased during the rainy season due to high ion-dilution.…”
Section: Discussionsupporting
confidence: 90%
“…The temperature results indicate the degree of heating that the water was exposed to through the solar radiation, and vary with season but can remain stable in the same regions [28]. The temperatures obtained from the two seasons were within the range considered to be normal, with an average of 25.88 °C obtained for the dry period and 24.77 °C for the rainy season.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…De acordo com Kreischer et al (2012), os valores de cor aparente são menores no período de chuva, devido ao efeito de diluição, diminuindo a intensidade de cor. Em contrapartida, Piratoba et al (2017), mencionam que com o aumento das chuvas, aumenta o transporte de material orgânico e inorgânico drenado nas margens dos rios, o que influência um aumento na cor. Os mesmos autores afirmam ainda, que a sazonalidade, a localização dos pontos de amostragem e a interação entre os dois fatores têm influência significativa na cor.…”
Section: Caracterização Da Qualidade Da áGuaunclassified